Influence of selected factors toward entrepreneurial career intentions among students of community colleges in selected states of Malaysia - Te, Tie Seng (2019)
Although many past studies have shown that community college students have high level of entrepreneurial intentions, but the number of community college graduates who chose to pursue entrepreneurial career after the completion of their studies are still less favourable. Besides that, despite there are many past studies involving community college students, there is still lack of studies involving states which have recorded a high rate of self-employment. Therefore, this study was conducted to identify the relationship between the selected factors and entrepreneurial career intentions among students of community college from the selected states. The selected factors in this study are attitude towards entrepreneurship, subjective norms, entrepreneurial self-efficacy and entrepreneurial exposure. This correlational research was theoretically based on the Theory of Planned Behaviour (TPB) by Ajzen (1991) and Social Cognitive Career Theory (SCCT) by Lent, Brown and Hackett (1994). This study consisted of 265 community college students in Kedah, Pahang and Perak. Cluster random sampling was applied in selecting the samples. The Pearson Correlation (r) and multiple regression analysis were used as the main inferential statistical analysis for this study. The instrument used was modified based on several sources of past studies and had gone through a content validity process. The instrument has a reliability value with a Cronbach α value between 0.75 to 0.91. The results indicate that all the selected factors have a positive and significant correlation with entrepreneurial career intentions. Attitude towards entrepreneurship was found to have a strong correlation with entrepreneurial career intentions (r=.597, p<.01). Meanwhile, entrepreneurial self-efficacy (r=.362, p<.01) and subjective norms (r=.327, p<.01) had a moderate correlation with entrepreneurial career intentions. Entrepreneurial exposure (r=.263, p<.01) was reported to have a low correlation with entrepreneurial career intentions. As a conclusion, all the selected factors showed a significant and positive relationship with entrepreneurial career intentions. Among all the selected factors, attitude towards entrepreneurship exerts the strongest influence toward entrepreneurial career intentions. This indicates that if the students have positive perceptions toward the benefits and outcomes of entrepreneurial career, they are likely to pursue an entrepreneurial career. Thus, it is important that entrepreneurship education in community college focuses on raising students’ awareness regarding the benefits and outcomes of entrepreneurial career in order to encourage more students to pursue entrepreneurial career. This study provides an enriched contribution to the knowledge and significant implication to the practices of entrepreneurship. This study also signals to policy makers as well as entrepreneurship educators to further nourish the entrepreneurial career intentions among the students, so that it can be turned into actual entrepreneurial behaviour.